The influence of the choice of foreign policy strategies of the Republic of Serbia and Montenegro on the development of their bilateral military relations - Spasojević Čedo D. (Војно дело)
n a complex system of international relations and current geopolitical and security architecture at the global level, states, in accordance with their economic, military and other potentials, choose foreign policy strategies. In that regard, small states have a specific challenge making that choice given their limited capacities. Notwithstanding numerous classifications of small state foreign policy strategies that exist in the scientific community, they can essentially be reduced to two: the choice of a protector (in a form of an alliance or a powerful state) or the declaration of political/military neutrality. The different choice made by small countries in this matter can often be one of the obstacles in the development of their mutual bilateral relations, bearing in mind that choosing a certain foreign policy strategy implies actions that are often opposed to the interests of other countries. This particularly refers to the development of bilateral relations in sensitive foreign policy segments of small states, such as defence and security. The subject of the paper is the very analysis of this phenomenon on a concrete example, i.e. the examination of the impact of the different choice of foreign policy strategies of Serbia and Montenegro on the development of their mutual bilateral military relations, in the period after the dissolution of the State Union of Serbia and Montenegro. The aim of the paper is to determine possible connection between the non-complementarity of foreign policy courses of Serbia and Montenegro and the dynamics in the development of their bilateral military relations. The basic hypothesis is that Montenegro's choice of protector strategy through NATO membership and Serbia's strategy of military neutrality represent a serious obstacle in the development of their overall and especially bilateral military relations. Using content analysis, discourse analysis and comparative methods, the paper tried to prove the existence of a link between the oscillations in the bilateral military relations between Serbia and Montenegro and the dynamics in the choice of their foreign policy strategies. The paper is going to show that the actions undertaken by Montenegro within the framework of profiling its foreign policy strategy and efforts to become a member of NATO directly affected the weakening of the dynamics in the strengthening of bilateral military relations with Serbia, and that Serbia's neutral military policy and its shift away from Atlantic integration make it difficult to improve those relations. It can be concluded that the relations determined in such a way will remain dominant in the upcoming period as well, regardless of occasional publicly expressed intentions by both countries of mutual improvement of bilateral military relations, and especially in the circumstances of the current polarization in the relations between great powers after the beginning of the war in Ukraine in early 2022.